Plan of the temple comprising mandapa, antarala and a garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The foundation of this temple or subsidiary shrine (II), within the temple complex, suggests that this temple consisted of a mandapa, shallow antarala and a garbhagriha on the plan. Only the base mouldings of the temple survive.